A STUDY OF ENGLISH IDIOMS RELATING TO “ LOVE “ WITH REFERENCE TO THE VIETNAMESE EQUIVALENT / Chu Thị Minh Hương; NHDKH Dr. Nguyen Thi Thu Huong - Chu, Thị Minh Hương
To become proficient at English, one of the important and essential steps for learners is clearly to know how to use fluently English idioms as well as understand it in native language. In a simple term, it is useful and favorable for learners to make use of succinct style of language to express meaningful thinking such as human feelings, traditional quotes and sayings, specific contexts and so on. In both of Western and Eastern literature, Love is probably the most ideal emotion for using idioms to define. The purposes of this study are to examine in which methods and conditions are used to express the feeling “love” as well as to make some evaluations and comparisons between Vietnamese and English idioms. To achieve the purposes above, sources and information are carefully gathered and selected through searching a varied of studies and scholar journals about idioms, both in English and Vietnamese. After analyzing and evaluating for more apparent views of the thesis’s aspects, the result will indicate that there are both similarities and disimilarities between English idioms and Vietnamese ones in terms of syntactic and semantic features.